1994
DOI: 10.1128/jcm.32.9.2312-2314.1994
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Borrelia burgdorferi DNA in urine samples from healthy humans whose sera contain B. burgdorferi-specific antibodies

Abstract: Since the possibility of asymptomatic infection with Borrelia burgdorferi has been suggested by a positive serology found in healthy subjects, we hypothesized that these subjects might excrete borrelial DNA sequences in urine as happens in patients with Lyme borreliosis. We found borrelial sequences by nested PCR in the urine samples from 3 of 13 healthy B. burgdorferi antibody-positive adults but not in urine samples from 79 antibody-negative healthy controls. After therapy with doxycycline, the urine samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The effect of treatment correlates well with a PCR study of blood donors (79). Three patients with urine positive in PCR were found among 13 seropositive healthy adult blood donors.…”
Section: Monitoring Of Treatment Efficacysupporting
confidence: 75%
See 2 more Smart Citations
“…The effect of treatment correlates well with a PCR study of blood donors (79). Three patients with urine positive in PCR were found among 13 seropositive healthy adult blood donors.…”
Section: Monitoring Of Treatment Efficacysupporting
confidence: 75%
“…In addition to reports summarized in Table 7, B. burgdorferi DNA was detected by PCR in blood (189), SF (140,165), CSF (101), and urine (52,79,105,155,189) of patients with LA. Maiwald et al (105) found that 11 of 15 patients with LA (1 with arthralgia and a typical history of a tick bite and EM, 9 with arthritis as a major symptom with other etiologies ruled out, and 5 with arthritis in combination with other manifestations) were reactive on tests of urine by a PCR that amplified a 259-bp fragment of the 23S rRNA gene (161).…”
Section: Patients With Joint Manifestationsmentioning
confidence: 88%
See 1 more Smart Citation
“…In different studies, the rates of detection of borrelial DNA by PCR have ranged from 11 to 100% for urine samples from patients with neuroborreliosis (2,6,18,19,22,34), from 38 to 60% for patients with Lyme arthritis (19,34), and from 44 to 49% for patients with active LB (11,23). We were not able to confirm the presence of borrelial DNA in the urine of patients with early-stage localized or late-stage skin borreliosis.…”
Section: Discussionmentioning
confidence: 64%
“…Recently, promising results were published about the detection of borrelial DNA in the urine of patients with neuroborreliosis and Lyme arthritis (2,6,34,42). However, the diagnostic value of urine PCR in early infection is still unclear, and published results are controversial (18,19,22,23).…”
mentioning
confidence: 99%